Strategi Konten Media Sosial Dai Populer: Analisis Isi Instagram @husein_hadar - Sari, Wasvita; Setiawan, Muhyiddin Fanda; Amal, Ikrimatul (Jurnal Media dan Komunikasi Indonesia, 2026)
The digital revolution is transforming the arena of Islamic preaching (dakwah) from the traditional pulpit to social media, positioning Islamic preachers (dai) as influencers. In the context of communication studies, this phenomenon raises an intriguing question regarding how a religious figure establishes authority and influences an audience on new media platforms that tend to dismantle traditional hierarchies. This research examines this issue by analyzing the content strategy of Habib Ja’far on his Instagram account, @husein_hadar. The study aims to understand how the strategy of his preaching content is constructed, represented, and influences the success of the content on social media, particularly for the target audience of Generation Z and millennials. The research employed a qualitative content analysis method with a constructivist paradigm. The researcher analyzed 150 Instagram content pieces, consisting of the most popular (top posts) and the least popular (weakest posts) over a five-year period. Data analysis utilized the three stages of Corbin and Strauss’ coding: open coding, axial coding, and selective coding. The findings indicate an increase in the trend of video content and professional, trendy production quality, while image-based content and amateur quality have declined. Entertainment content was consistently dominant in the top post category, whereas news and invitation-based content never achieved success. It is concluded that Habib Ja’far employs strategies of message effectiveness, personal branding, and celebrity endorsement in his dakwah.